The evaluation of cardiac functions in deep Trendelenburg position during robotic-assisted laparoscopic prostatectomy - Kılınç, Emir; Yildirim, Serap Aktas; Ulugöl, Halim; Büyüköner, Elif Eroğlu; Güçyetmez, Bülent; Toraman, Fevzi (Frontiers in Medicine, 2023)
Objective This study aimed to demonstrate the reliability of the cardiac cycle efficiency value through its correlation with longitudinal strain by observing the effect of the deep Trendelenburg position. Design A prospective, observational study. Setting Single center. Participants Between May and September 2022, the hemodynamic parameters of 30 patients who underwent robotic assisted laparoscopic prostatectomy under general anesthesia were prospectively evaluated. Measurements and main results All invasive cardiac monitoring parameters and longitudinal strain achieved transesophageal echocardiography were recorded in pre-deep Trendelenburg position (T3) and 10th minute of deep Trendelenburg position (T4). Delta values were calculated for the cardiac cycle efficiency and longitudinal strain (values at T4 minus values at T3). The estimated power was calculated as 0.99 in accordance with the cardiac cycle efficiency values at T3 and T4 (effect size: 0.85 standard deviations of the mean difference: 0.22, alpha: 0.05). At T4, heart rate, pulse pressure variation, cardiac cycle efficiency, dP/dt and longitudinal strain were significantly lower than those at T3 (p = 0.009, p < 0.001, p < 0.001, and p < 0.001, respectively). There was a positive correlation between the delta-cardiac cycle efficiency and delta-longitudinal strain (R2 = 0.36, p < 0.001). Conclusion Although the absence of significant changes in mean arterial pressure and cardiac index after Trendelenburg position suggests that cardiac workload has not changed, changes in cardiac cycle efficiency and longitudinal strain indicate increased cardiac workload due to increased ventriculo-arterial coupling.